1984
DOI: 10.1007/bf00253493
|View full text |Cite
|
Sign up to set email alerts
|

Tolbutamide does not alter insulin requirement in Type 1 (insulin-dependent) diabetes

Abstract: We examined whether tolbutamide has any acute or short-term effects on insulin action in Type 1 (insulin-dependent) diabetes. A euglycaemic glucose clamp was performed in seven Type 1 diabetic patients without clinical insulin resistance by infusing glucose at a constant rate of 0.01 mmol X kg-1 X min-1 for 3h together with a simultaneous insulin infusion using an 'artificial pancreas'. The insulin infusion rate required to maintain blood glucose at 6.7 mmol/l at a set low glucose infusion rate provides an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Tolbutamide has been found to increase glucagon secretion in isolated rat ␣-cells (16) and in insulin-deficient type 1 diabetes in some (17) but not all (18) studies, and in the present studies in patients with advanced type 2 diabetes, plasma glucagon tended to be greater during the infusion of tolbutamide than during the infusion of saline. It may therefore be argued that the increased glucagon responses following tolbutamide may be explained by ongoing stimulation of glucagon secretion or simply greater plasma glucagon levels immediately before inducing hypoglycemia.…”
Section: Plasma Counterregulatory Hormonessupporting
confidence: 58%
“…Tolbutamide has been found to increase glucagon secretion in isolated rat ␣-cells (16) and in insulin-deficient type 1 diabetes in some (17) but not all (18) studies, and in the present studies in patients with advanced type 2 diabetes, plasma glucagon tended to be greater during the infusion of tolbutamide than during the infusion of saline. It may therefore be argued that the increased glucagon responses following tolbutamide may be explained by ongoing stimulation of glucagon secretion or simply greater plasma glucagon levels immediately before inducing hypoglycemia.…”
Section: Plasma Counterregulatory Hormonessupporting
confidence: 58%
“…Given the extreme sensitivity of liver for small changes in the insulin concentration, it is quite possible that small changes in portal insulin concentrations have been overlooked. (4) There have also been difficulties in confirming initial reports of increased insulin binding during sulfonylurea therapy (GRUNBERGER et al 1982;RATZMANN et al 1984;DOLAIS-KITABGI et al 1983). (5) Finally, and probably most important, chronic hyperglycemia can cause both peripheral and hepatic insulin resistance, which can be attenuated by improved glucose control independently of the mode of treatment (YKI-JÄRVINEN 1990;ROSSETTI et al 1987).…”
Section: Extrapancreatic Effectsmentioning
confidence: 88%
“…(1) Sulfonylureas do not reduce plasma glucose in pancreatectomized animals or in patients with type 1 diabetes (MIRSKY et al 1956;HOUSSAY and PENHOS 1956;GRUNBERGER et al 1982;RATZMANN et al 1984), or in NIDDM patients made insulinopenic with somatostatin (WIDEN 1993). (2) Early studies examining the extrapancreatic effects of sulfonylureas did not appreciate the problem with restudying patients at identical plasma glucose levels.…”
Section: Extrapancreatic Effectsmentioning
confidence: 97%
“…Based on results obtained in insulin-dependent diabetic patients where sulphonylurea have failed to lower blood glucose [41,42] it has been argued that any change in tissue insulin sensitivity during longterm sulphonylurea treatment may be due to improved metabolic control induced by the pancreatic effects of the drugs. Other investigators [43] have, however, reported that after 6 weeks of glyburide administration, total whole body glucose uptake improved in healthy control subjects despite unchanged fasting levels of serum insulin and plasma glucose.…”
Section: Discussionmentioning
confidence: 99%